Expedient Synthesis of the Pentasaccharide Repeating Unit of the Polysaccharide O‐Antigen of Escherichia coli O11. Issue 1 (27th July 2015) - Si, Anshupriya; Misra, Anup Kumar
Abstract: A convergent [3+2] block synthetic strategy was developed for the synthesis of the pentasaccharide repeating unit of the cell wall O‐antigen of Escherichia coli O11 strain in excellent yield in a minimum number of steps. Several suitably functionalized thioglycoside derivatives were used as glycosyl donors during the synthesis of the target compound. A thioglycoside was the glycosyl donor used to couple with another thioglycoside derivative in a highly stereoselective manner exploiting the difference of their reactivity profile. A combination of N iodosuccinimide (NIS) and perchloric acid supported over silica gel (HClO4 −SiO2 ) was used as a thiophilic glycosylation activator system in all stereoselective glycosylation reactions. HClO4 −SiO2 acted as a user‐friendly solid acid catalyst. Yields were very good in all glycosylation steps with a high stereoselective outcome. The synthetic pentasaccharide could be coupled to an appropriate protein to furnish a glycoconjugate derivative for its use in immunochemical studies. Abstract : Sugar synthesis for E. coli O11 : A pentasaccharide corresponding to the repeating unit of the cell wall O‐antigen of Escherichia coli O11 strain was synthesized using a stereoselective block glycosylation approach. A thioglycoside was used as the glycosyl donor to couple with another thioglycoside derivative in a highly stereoselective manner by tuning their relative reactivity profile. All glycosylation steps were highly stereoselective with satisfactory yields.